Kepastian Hukum Memorandum Of Understanding (Mou) Pada Kondisi Pandemi Covid-19 Dalam Hukum Perjanjian Indonesia - Jamil, Nury Khoiril; Basri, Achmad Hasan; Sutopo, Urmawan (Acta Comitas : Jurnal Hukum Kenotariatan, 2022)
The objective of this paper is to examine the legal certainty of the Memorandum of Understanding during Covid-19 pandemic in the treaty law which applies in Indonesia. In addition, it is also to find out the resolution of disputes when one of the parties breaks a promise. The study used normative juridical methods with law enforcement approaches, law concept analysis and case aprroach. The results of this study are the position of the MoU during the pandemic requires an observation of the substance contained in the MoU. If a MoU contains an element of material financial loss, if the performance is not fulfilled, it  is punishable. If the parties disprove it, the MoU has already been established as a contract agreement based on Articles 1338 and 1320 of the Civil Code. In the other word means while it is not explicitly stated as a contract, but based on the de facto theory (implied in fact) the MoU would be categorized as a contract. While the MoU only regulates the basic provisions that emphasize the moral burden  than the current pandemic situation. So, depart from it, when the law is not explicitly set about the MoU, at that time a judge must explore and identify the law. It can be found by investigating legal values ??that arise in society by adjusting to current circumstances, especially the pandemic situation through interpretation to build legal constructions that can fill legal voids which may later become jurisprudence.